2005
DOI: 10.2209/tdcpublication.46.7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Large Tubules and Dentin Caries in Human Deciduous Tooth

Abstract: The purpose of this study was to elucidate the relationship between large tubules and dentin caries by using human deciduous incisors that showed various levels of attrition but no macroscopical lesions resulting from caries. The teeth were cut longitudinally in the mesio-distal direction and the exposed surfaces observed with a high-resolution field emission scanning electron microscope. The inside of each large tubule showed dense collagen fibers running parallel to its long axis and small spherical bodies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…The behavior of dental tissue in response to thermal stimuli depends on the physiological characteristics of the tooth. Primary teeth have larger dentin tubule structures than those of permanent teeth, which increases the permeability of primary teeth and causes them to be more easily affected by external stimuli (5). Dentin and its geometric structure additionally play an important role in the increase of heat.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of dental tissue in response to thermal stimuli depends on the physiological characteristics of the tooth. Primary teeth have larger dentin tubule structures than those of permanent teeth, which increases the permeability of primary teeth and causes them to be more easily affected by external stimuli (5). Dentin and its geometric structure additionally play an important role in the increase of heat.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the penetration of viable S. mutans bacteria in dentinal tubules was found to be up to 95.9, 92.1, and 92.7 μm in group I; 116.3, 93.1, and 84.2 μm in group II; and 128.9, 138.7, and 131.8 μm in group III at 60, 120, and 180 seconds, respectively. Whereas Agematsu et al 24 reported that the oral bacteria can invade up to 250 μm from the open end in deciduous anterior teeth, while Sen et al 25 observed through scanning electron microscope (SEM), the depth of bacterial penetration into dentinal tubules of root canal ranged from 10 to 150 μm. This variation may be due to different study designs, and preparation of samples, as for SEM, dehydrated samples were used, whereas in our study, no dehydration of samples was done since laser scanning confocal microscopy (LSCM) allows the evaluation of samples without the need for dehydration and, thus, the true native morphology of teeth was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although primary teeth have dentin with a lower degree of mineralization compared to permanent teeth dentin, 13 larger dentinal tubular structures of the primary teeth than those of the permanent teeth may increase the permeability of primary teeth and make them more susceptible to thermal stimuli. 14 Therefore, there was a need to conduct studies on primary teeth due to the inability to rely on the results of studies conducted on permanent teeth.…”
Section: Introductionmentioning
confidence: 99%